2012
DOI: 10.4172/1948-5948.1000083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levofloxacin and Vitamin C on Bacterial Adherence and Preformed Biofilm on Urethral Catheter Surfaces

Abstract: The effect of levofloxacin (LEV) and vitamin-C (VIT-C) individually or in combinations on initial bacterial adherence and pre-formed (mature) biofilms on the surface of urethral catheters was studied. The isolated and studied uropathogens in the present study showed considerable diversity, where the major pathogens were identified as E.coli, Klebsiella sp., Citrobacter sp., Enterobacter sp., Proteus sp. and Pseudomonas sp. Using the static adherence assay, addition of LEV and VIT-C each alone at sub MIC concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
3
24
1
Order By: Relevance
“…Several authors have already described the bacteriostatic activity of AA against Staphylococcus aureus, 18,19) as well as its synergy with some antibiotics. 20,21) Interesting results were obtained for Pseudomonas aeruginosa 22,23) alone and in the presence of an antibiotic 24) and for Candida albicans. [25][26][27] Escherichia coli seems to be inhibited in some conditions in the presence of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have already described the bacteriostatic activity of AA against Staphylococcus aureus, 18,19) as well as its synergy with some antibiotics. 20,21) Interesting results were obtained for Pseudomonas aeruginosa 22,23) alone and in the presence of an antibiotic 24) and for Candida albicans. [25][26][27] Escherichia coli seems to be inhibited in some conditions in the presence of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Double fold serially diluted MNPs (OA-MNPs and APTMS-MNPs) were added in all wells except in negative control wells and incubated at 37 ∘ C for 24 h to evaluate the effect of MNPs on preformed biofilms. MNPs were discarded and the remaining biofilms were stained with CV as previously described [26]. diluted MNPs (except negative control wells) and incubated at 37 ∘ C for 24 h. Residual living cells were treated with 20 L sterile 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) dye (5 mg/mL) at 37 ∘ C for 4 h. MTT was discarded and plates were washed with PBS three times.…”
Section: Effect On Preformedmentioning
confidence: 99%
“…Similar results against mature biofilms of uropathogenic bacteria (E. coli, Klebsiella spp., Citrobacter spp., Enterobacter spp., Proteus spp., and Pseudomonas spp.) have been reported by El-Gebaly et al [31]. On the contrary, other studies [30,[32][33][34] have found that ascorbic acid did not inhibit the growth of E. coli and P. aeruginosa but made them more resistant to antimicrobials and physical disinfection.…”
Section: Discussionmentioning
confidence: 84%